Genome-wide DNA methylation of lesional and peri-lesional skin in vitiligo: a comparative and integrated analysis of multi-omics in Chinese population - Liu, Lin; Xue, Yuzhou; Li, Yuxin; Chen, Yangmei; Pan, Xingyu; Huang, Yujing; Chen, Tingqiao; Zhong, Judan; Shao, Xinyi; Pu, Yihuan; Chen, Jin (Human genetics, 2024)
Several studies have emphasized the role of DNA methylation in vitiligo. However, its profile in human skin of individuals with vitiligo remains unknown. Here, we aimed to study the DNA methylation profile of vitiligo using pairwise comparisons of lesions, peri-lesions, and healthy skin. We investigated DNA methylation levels in six lesional skin, six peri-lesional skin, and eight healthy skin samples using an Illumina 850 K methylation chip. We then integrated DNA methylation data with transcriptome data to identify differentially methylated and expressed genes (DMEGs) and analyzed their functional enrichment. Subsequently, we compared the methylation and transcriptome characteristics of all skin samples, and the related genes were further studied using scRNA-seq data. Finally, validation was performed using an external dataset. We observed more DNA hypomethylated sites in patients with vitiligo. Further integrated analysis identified 264 DMEGs that were mainly functionally enriched in cell division, pigmentation, circadian rhythm, fatty acid metabolism, peroxidase activity, synapse regulation, and extracellular matrix. In addition, in the peri-lesional skin, we found that methylation levels of 102 DMEGs differed prior to changes in their transcription levels and identified 16 key pre-DMEGs ( ANLN, CDCA3, CENPA, DEPDC1, ECT2, DEPDC1B , HMMR, KIF18A, KIF18B, TTK, KIF23, DCT, EDNRB, MITF, OCA2, and TYRP1) . Single-cell RNA analysis showed that these genes were associated with cycling keratinocytes and melanocytes. Further analysis of cellular communication indicated the involvement of the extracellular matrix. The expression of related genes was verified using an external dataset. To the best of our knowledge, this is the first study to report a comprehensive DNA methylation profile of clinical vitiligo and peri-lesional skin. These findings would contribute to future research on the pathogenesis of vitiligo and potential therapeutic strategies.